Safety of intravenous tranexamic acid in patients undergoing supratentorial meningiomas resection: protocol for a randomised, parallel-group, placebo control, non-inferiority trial. Issue 2 (2nd February 2022) - Li, Shu; Yan, Xiang; Li, Ruowen; Zhang, Xingyue; Ma, Tingting; Zeng, Min; Dong, Jia; Wang, Juan; Liu, Xiaoyuan; Peng, Yuming
Abstract : Introduction: Growing evidence recommends antifibrinolytic agent tranexamic acid (TXA) to reduce blood loss and transfusions rate in various surgical settings. However, postoperative seizure, as one of the major adverse effects of TXA infusion, has been a concern that restricts its utility in neurosurgery. Methods and analysis: This is a randomised, placebo-controlled, non-inferiority trial. Patients with supratentorial meningiomas and deemed suitable for surgical resection will be recruited in the trial. Patients will be randomised to receive either a single administration of 20 mg/kg TXA or a placebo of the same volume with a 1:1 allocation ratio after anaesthesia induction. The primary endpoint is the cumulative incidence of early postoperative seizures within 7 days after craniotomy. Secondary outcomes include the incidence of non-seizure complications, changes of haemoglobin level from baseline, intraoperative blood loss, erythrocyte transfusion volume, Karnofsky Performance Status, all-cause mortality, and length of stay, and total hospitalisation cost. Ethics and dissemination: This trial is registered at ClinicalTrial.gov and approved by the Chinese Ethics Committee of Registering Clinical Trials (ChiECRCT20200224). The findings will be disseminated in peer-reviewed journals and presented at national or international conferences relevant to subject fields. Trial registration number: NCT04595786 .